Strategi Indonesia Menghadapi Krisis Pangan, Energi, Dan Iklim - magfiroh, Diana (Fakultas Ekonomi Universitas Gresik, 2024)
Indonesia faces multidimensional challenges due to the intertwined food, energy, and climate crises that exacerbate structural inequalities in sustainable development. These interconnected crises are characterized by a 15.8% decline in food productivity (from 95 to 80 million tons), a 36% increase in fossil fuel-based energy consumption (from 220 to 300 TWh), and a 22% surge in carbon emissions (from 450 to 550 million tons CO₂) over the period 2015-2023, collectively threatening national resilience across economic, social, and ecological dimensions. This study aims to analyze systemic linkages between sectors, evaluate existing policies, and formulate adaptive, evidence-based integrative strategies. Employing a mixed-methods approach, this research combines quantitative analysis of secondary data from authoritative sources (BPS, FAO, IEA, IPCC) and qualitative analysis through in-depth interviews with 15 experts representing government ministries, academic institutions, and NGOs. The analytical technique involves dynamic system modeling to simulate three policy scenarios: Business as Usual, Green Transition, and Integrated Resilience. Findings demonstrate that sectoral policies operating in silos are insufficient to effectively address this crisis. The Integrated Resilience scenario proved most effective, projecting a reduction in energy consumption to 280 TWh (20% lower than Business as Usual), carbon emissions to 450 Mt CO₂ (25% reduction), and an increase in food production to 90 Mt (12.5% improvement) by 2030. Furthermore, national institutions still exhibit low levels of policy integration, characterized by fragmented programs across sectors and inadequate inter-ministerial coordination mechanisms. These findings underscore the need for data-driven, collaborative, and systemic policy reformulation to ensure long-term national resilience and sustainable development pathways.